THE STUDY OF THE ACCEPTANCE OF FISH BALL WITH THE ADDITION OF NOURISHMENT OF BANANA KEPOK HEART FLOUR (Leptobarbus hoevenii) - Sudiono, Nanang; ', Desmelati; ', Sumarto (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
This study aims to determine the effect of the addition of banana kepok heart meal to the acceptance of jelly fish ball jelawat. The method used was experiments, with Completely Randomized Design (RAL) of one factor as the treatment was the addition of banana flour banana flour which consists of 4 treatment levels: B0 (without banana flour), B1 (banana flour 25 g) B2 (banana fiber flour 50 g) and B3 (banana flour 75 g). The parameters tested were organoleptic and chemical. The results showed that based on the parameters tested for the best treatment of consumer acceptance of jelly fish tball jelawat was the addition of banana fiber flour 50 g (B2), with the criteria of rounded, uniform, slightly hollow form, creamy brown, compact texture, solid and somewhat chewy, the aroma with the criteria is not fishy, the fish meatball specific is slightly reduced, and the taste is rather tasty, the fish taste less with moisture value 25,86%, protein 15,19%, fat 7,80%, crude fiber 7,73 % and ash content 3.97%.Keywords: banana kepok heart flour, jelawat fish, fish ball